Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2023)
Table of Content:1. Mohamed ‘Ali Al-Tajer and His Book ‘Aqd al-La’al fi Tarikh Awal: A Critical reading of its content in the history of BahrainCo-Prof. Khalid Ismail Nayif Al-Hamadani2. The ideal theory in Plato’s Philosophy and it’s relevance to man and the universeMrs. Nadha Mutlaq ALbogami3. Reality and challenges of the work environment of Agricultural Engineers working in the private and non-governmental sectors in the West Bank, Palestine considering some variablesMr. Salem Nassr, Mrs. Doaa Zayed4. The motives of the Sudanese citizen's use of YouTube and the gratifications achieved from it sample of citizens of Khartoum State for the year 2023Co-Prof. Badereldin Ali Hamed Mohammed5. An analysis of political speeches on racism by President Donald Trump during his presidencyMrs. Brooj Nasser A. Alsaqer6. Images of Arabs and Islam in Burton’s Pilgrimage to Al-Madinah and MeccahMr. Abdulkarim Mohammad Alseadoon, Dr. Geoffrey Nash7. The Translation of Yemeni – Arabic legal documents into English: Problems and SuggestionsMrs. Hakima Mansour Ahmed Khoshafah
Keywords: Arab Journal of Sciences & Research Publishing